2012
DOI: 10.1007/s10238-012-0192-7
|View full text |Cite
|
Sign up to set email alerts
|

Negative effect of immunosuppressive therapy in the performance of the QuantiFERON Gold In-Tube test in patients with immune-mediated inflammatory diseases

Abstract: To compare the tuberculin skin test (TST) and QuantiFERON-TB Gold In-Tube test (QFG) for the detection of latent tuberculosis infection among patients with immune-mediated inflammatory diseases before antitumor necrosis factor-α therapy. A prospective study including 153 consecutive patients with rheumatoid arthritis (n = 53), psoriasis (n = 45), inflammatory bowel disease (n = 25), and spondyloarthropathy (n = 22) were included. QFG and TST were performed simultaneously. TST was positive in 43/153 (28.1 %) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 32 publications
2
35
0
1
Order By: Relevance
“…Immunosuppressive treatments, including biologics, are also known to cause a decrease in the production of IFN-c, which, in turn, could reduce the accuracy of QFT-GIT testing. 34 Our results are consistent with those of Higuchi et al, 35 who showed that 25% of those who were positive for QFT-GIT before isoniazid became negative after treatment. Data regarding the efficacy of isoniazid prophylaxis in patients with psoriasis and LTBI receiving biological therapy are scarce.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Immunosuppressive treatments, including biologics, are also known to cause a decrease in the production of IFN-c, which, in turn, could reduce the accuracy of QFT-GIT testing. 34 Our results are consistent with those of Higuchi et al, 35 who showed that 25% of those who were positive for QFT-GIT before isoniazid became negative after treatment. Data regarding the efficacy of isoniazid prophylaxis in patients with psoriasis and LTBI receiving biological therapy are scarce.…”
Section: Discussionsupporting
confidence: 95%
“…13,33 Causes of variability in serial IGRA testing could be intrinsic to the assay or due to variability in the immune response. 34 Potential causes of intra-assay variability include improper collection, storage, incubation and processing of blood tubes, and variation of the IFN-c measurement. Potential sources for variable immune responses include medications and infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnostic value of IGRA is being questioned in patients with immune-mediated inflammatory diseases, such as psoriasis. 25 In conclusion, the use of a screening tool for LTBI is mandatory in patients taking biologic therapies to avoid severe infectious complications due to the increased risk of TB infections (pulmonary, extrapulmonary, and disseminated) in this population. Periodic follow-up is also crucial as positive results may be seen after prolonged use of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal strategy in IBD patients has not been yet well-defined as both TST and QFT-G-IT may be negatively affected by disease activity and/or treatment with immunomodulators (IMM), such as azathioprine and methotrexate [6][7][8][9][10][11][12][13][14][15][16][17]. The sensitivity and specificity of TST in the diagnosis of LTB can be limited by high disease activity, malnutrition, treatment with IMM, prior Bacille Calmette-Guerin (BCG) vaccination and/or exposure to environmental mycobacteria [8,9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity and specificity of TST in the diagnosis of LTB can be limited by high disease activity, malnutrition, treatment with IMM, prior Bacille Calmette-Guerin (BCG) vaccination and/or exposure to environmental mycobacteria [8,9,18,19]. On the other hand, the sensitivity of QFT-G-IT may be compromised in patients with highly active disease, especially when they have low albumin levels, and in IMM-treated patients with a low lymphocyte count [68, [10][11][12][13]16,20,21]. Nevertheless, a higher accuracy and cost-effectiveness of IGRA compared to the TST has been reported in IBD patients with a prior BCG vaccination and/or on IMM therapy [9,22].…”
Section: Introductionmentioning
confidence: 99%